A Reference‐Scaled Average Bioequivalence Study of Azithromycin Tablets Manufactured in China and the United States: An Open‐Label, Randomized, Single‐Dose, 3‐Way Crossover Study in Healthy Chinese Subjects Under Fasted and Fed Conditions. Issue 10 (21st June 2022) - Ge, Beikang; Li, Cuiyun; Wei, Hua; Ding, Yanhua; Wu, Min; Liu, Yuwang; Zhang, Kaiting; Peng, Ao
Abstract: Azithromycin (Zithromax) is an azalide antibiotic that binds to the 50S ribosomal subunit of the susceptible organism and thereby interferes with its protein synthesis. An open‐label, randomized, single‐dose, 3‐way crossover bioequivalence study was conducted to compare the rate and extent of absorption of the azithromycin 250‐mg tablet manufactured at Pfizer Dalian (China) and that at Pfizer Barceloneta (United States) under fasted and fed conditions in healthy Chinese subjects. This study aimed to support a generic consistency evaluation program, initiated by the National Medical Products Administration, for evaluating the quality and efficacy of the products manufactured in China. In the study, the within‐subject standard deviation for area under the serum concentration–time profile from time 0 to 72 hours after dosing in the fasted condition was <0.294, and the 90%CI for the ratio was within 80% to 125%; the within‐subject SDs for serum peak concentration in the fasted condition, area under the serum concentration–time profile from time 0 to 72 hours after dosing in the fed condition, and serum peak concentration in the fed condition, were all >0.294, with the upper confidence bounds being <0.00, and the point estimates of the ratios being within 80% to 125%. The results support the bioequivalence between azithromycin tablets manufactured in China and the United States in fasted and fed conditions, with both tablets showing an acceptable safety/tolerability profile in the studied population.